Public Investment Management in Contexts of Fragility, Conflict & Violence – Part 1 - Cuvillier, Emmanuel (World Bank, Washington, DC, 2019)
A government's provision of complementary public goods, such as roads and bridges, facilitates the development of markets leading to long-term economic growth. Private enterprise, by itself, is unlikely to provide such public works. Likewise, a government's investment in social infrastructure, such as education and health, is critical, particularly for conflict-ridden populations deprived of adequate services. Furthermore, scaling-up public investment is central to development, especially in in FCV contexts, which are often left with rudimentary or badly-damaged infrastructure. Public investments in FCV countries are often inefficient and ineffective, prone to waste, corruption and misappropriation. They are often highly concentrated in a few units or agencies with weak institutional capacity. Thus, supporting better management of public investments in FCV countries is critical to (re)creating economic and social infrastructure. This infrastructure is key to quickly restore basic services and the reestablishment of trust between the state and citizens. As such, it can allow for citizens to reap early peace dividends and plant the seeds for long-term stability.